Smart responsive Fe/Mn nanovaccine triggers liver cancer immunotherapy via pyroptosis and pyroptosis-boosted cGAS-STING activation - Qianying Du; Ying Luo; Lian Xu; Chier Du; Wenli Zhang; Jie Xu; Yun Liu; Bo Liu; Sijin Chen; Yi Wang; Zhigang Wang; Haitao Ran; et al. (Journal of Nanobiotechnology, 2024)
Abstract Background The prognosis for hepatocellular carcinoma (HCC) remains suboptimal, characterized by high recurrence and metastasis rates. Although metalloimmunotherapy has shown potential in combating tumor proliferation, recurrence and metastasis, current apoptosis-based metalloimmunotherapy fails to elicit sufficient immune response for HCC. Results A smart responsive bimetallic nanovaccine was constructed to induce immunogenic cell death (ICD) through pyroptosis and enhance the efficacy of the cGAS-STING pathway. The nanovaccine was composed of manganese-doped mesoporous silica as a carrier, loaded with sorafenib (SOR) and modified with MIL-100 (Fe), where Fe3+, SOR, and Mn2+ were synchronized and released into the tumor with the help of the tumor microenvironment (TME). Afterward, Fe3+ worked synergistically with SOR-induced immunogenic pyroptosis (via both the classical and nonclassical signaling pathways), causing the outflow of abundant immunogenic factors, which contributes to dendritic cell (DC) maturation, and the exposure of double-stranded DNA (dsDNA). Subsequently, the exposed dsDNA and Mn2+ jointly activated the cGAS-STING pathway and induced the release of type I interferons, which further led to DC maturation. Moreover, Mn2+-related T1 magnetic resonance imaging (MRI) was used to visually evaluate the smart response functionality of the nanovaccine. Conclusion The utilization of metallic nanovaccines to induce pyroptosis-mediated immune activation provides a promising paradigm for HCC treatment.